Una aproximación teórica a la valoración del doble ajuste en el dise\~no de la estrategia de recursos humanos - Natalia García Carbonell; Fernando Martín Alcázar; Gonzalo Sánchez Gardey (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– Traditionally, literature has considered the need of the double fit, vertical and horizontal fit, of the human resource strategy in organizations. Its strategic importance has been empirically demonstrated in different studies, however, the complexity of this process demands deeper theoretical analysis, which allows us to identify those elements that make the double fit possible. In this study, drawing on the main human resource management perspectives and the 'system strength' concept proposed by Bowen and Ostroff (2004), we discuss the three main features that define this concept and its relationship with the human resource system fit. As a consequence of our analysis, we establish three theoretical propositions that explain the link between the double fit and the system strength concept.
Keywords: M12; 330; Human resources; Vertical and horizontal fit; System strength